Representation of Gotong-Royong Local Wisdom in Toba Batak Folklore - Siagian, Rolas Tipando (L'Geneus : The Journal Language Generations of Intellectual Society, 2019)
Gotong royong is defined as working together, helping, helping. Those who carry out mutual cooperation are based on the same fate in society. They are together in joy and sorrow. In mutual assistance or mutual cooperation, there is an agreement or consensus for what, when, where, or where to work together, this must be discussed first. (Sibarani 2014: 9). There are also types of local wisdom in mutual cooperation, namely marsiurupan and marria raja. This can be seen from how they solve an activity or problem. The mutual assistance function of the three folk tales has two functions, namely a function for peace which includes politeness, honesty, social solidarity, harmony and conflict resolution, commitment, positive thoughts and gratitude, and also a function for welfare which includes work culture, discipline, mutual cooperation, education, health, gender processing, cultural preservation and creativity, and the environment. Judging from the contents of the story, shows that life in ancient times was very thick with mutual cooperation. Where often seen solving a problem / job by helping each other / mutual assistance (marsiurupan) to get more results or shorten the processing time. Even the perpetrators of gotong royong (gotong royong) will always help by voluntarily providing funds, food or limited energy to group members who need it at that time.